(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Establising and evaluating reference intervals for hematological parameters in adults at Le Van Thinh Hospital for examination and testing. Subject and method: A cross-sectional descriptive study was conducted from January 2023 to December 2023 involving 2368 individuals aged 18-28 (1179 males, 1189 females) who participated in health examinations and hematological testing at the Hematology- Blood Transfusion Department of Le Van Thinh Hospital. The results were analyzed using SPSS 20.0 software, calculating the mean values and standard deviations for normally distributed variables. Gender differences were compared using a t-test (for comparing means) with a significance level of p<0,05. Results: The reference ranges for RBC, HGB, HCT, MCV, MCH, and MCHC were higher in males compared to females (p<0,05); meanwhile, RDW was higher in females compared to males (p<0,05). There was no significant difference in the reference range for WBC between males and females (p>0,05); however, females had higher NEU counts compared to males. Males had higher LYM, MONO, and ESO counts compared to females. There was no significant difference in the reference range for BASO% between the two genders (p>0,05). The reference range for PLT was higher in females than males; whereas, MPV was higher in males than females (p<0,05) Conclusion: The reference intervals for hematological parameters were determined and evaluated at Le Van Thinh Hospital.